PECULIAR STARS IN THE SOUTHERN GALACTIC ECUATOR - MUNCH, LUIS (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
Peculiar Stars in the Southern Galactic Ecuator
BOL OBS TONAN TACUB
Keywords: PECULIAR STARS, SOUTHERN, GALACTIC ECUATOR; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS